Platelet-rich plasma gel in combination with Schwann cells for repair of sciatic nerve injury☆ - Ye, Fagang (Neural Regen Res, 2012)
Bone marrow mesenchymal stem cells were isolated from New Zealand white rabbits, culture-expanded and differentiated into Schwann cell-like cells. Autologous platelet-rich plasma and Schwann cell-like cells were mixed in suspension at a density of 1 × 10(6) cells/mL, prior to introduction into a poly (lactic-co-glycolic acid) conduit. Fabricated tissue-engineered nerves were implanted into rabbits to bridge 10 mm sciatic nerve defects (platelet-rich plasma group). Controls were established using fibrin as the seeding matrix for Schwann cell-like cells at identical density to construct tissue-engineered nerves (fibrin group). Twelve weeks after implantation, toluidine blue staining and scanning electron microscopy were used to demonstrate an increase in the number of regenerating nerve fibers and thickness of the myelin sheath in the platelet-rich plasma group compared with the fibrin group. Fluoro-gold retrograde labeling revealed that the number of Fluoro-gold-positive neurons in the dorsal root ganglion and the spinal cord anterior horn was greater in the platelet-rich plasma group than in the fibrin group. Electrophysiological examination confirmed that compound muscle action potential and nerve conduction velocity were superior in the platelet-rich plasma group compared with the fibrin group. These results indicate that autologous platelet-rich plasma gel can effectively serve as a seeding matrix for Schwann cell-like cells to construct tissue-engineered nerves to promote peripheral nerve regeneration.